Migration, fate and in vivo imaging of adult stem cells in the CNS - Syková, E; Jendelová, P (Cell death and differentiation, 2007)
Adult stem cells have been intensively studied for their potential use in cell therapies for neurodegenerative diseases, ischemia and traumatic injuries. One of the most promising cell sources for autologous cell transplantation is bone marrow, containing a heterogenous cell population that can be roughly divided into hematopoietic stem and progenitor cells and mesenchymal stem cells (MSCs). MSCs are multipotent progenitor cells that, in the case of severe tissue ischemia or damage, can be attracted to the lesion site, where they can secrete bioactive molecules, either naturally or through genetic engineering. They can also serve as vehicles for delivering therapeutic agents. Mobilized from the marrow, sorted or expanded in culture, MSCs can be delivered to the damaged site by direct or systemic application. In addition, MSCs can be labeled with superparamagnetic nanoparticles that allow in vivo cell imaging. Magnetic resonance imaging (MRI) is thus a suitable method for in vivo cell tracking of transplanted cells in the host organism. This review will focus on cell labeling for MRI and the use of MSCs in experimental and clinical studies for the treatment of brain and spinal cord injuries.
Keywords: Cell Movement; Cell Differentiation; Nanoparticles; Mesenchymal Stem Cell Transplantation; Central Nervous System; Mesenchymal Stem Cells; transplantace mezenchymálních kmenových buněk; Cell Lineage; magnetická rezonanční tomografie; mezenchymální kmenové buňky; barvení a značení; Magnetic Resonance Imaging; centrální nervový systém; buněčný rodokmen; zvířata; Humans; Staining and Labeling; pohyb buněk; nanočástice; buněčná diferenciace; lidé; Animals